2021
DOI: 10.1002/acn3.51312
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth peripheral CD4+ T profile correlates with myasthenic crisis

Abstract: Objective Myasthenia gravis (MG) is an autoimmune disease caused by autoantibodies against neuromuscular junctions. Myasthenic crisis (MC) represents the most severe state of MG with high in‐hospital mortality. We aimed to identify immune signatures using in‐depth profiling in MC, and to assess the correlations between immune biomarkers with clinical severity longitudinally. Methods We studied 181 participants including 57 healthy controls, 96 patients with MG who never experienced crisis and 28 MC patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Although these cytokines were elevated in current selected cohort, IL-4 and IL-12p70 level were previously revealed to be decreased in non-crisis MG patients compared with healthy controls [ 8 ]. We have two explanations for this discrepancy: (1) non-crisis gMG selected in previous study were mainly comprised of MGFA II-IV who had never had a crisis but 25% have already been on immunotherapy, which may lower the peripheral inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although these cytokines were elevated in current selected cohort, IL-4 and IL-12p70 level were previously revealed to be decreased in non-crisis MG patients compared with healthy controls [ 8 ]. We have two explanations for this discrepancy: (1) non-crisis gMG selected in previous study were mainly comprised of MGFA II-IV who had never had a crisis but 25% have already been on immunotherapy, which may lower the peripheral inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 90%
“…MG mimicking diseases including Lambert-Eaton myasthenic syndrome, peripheral neuropathy, myopathies, and motor neuron diseases were excluded before the recruiting. The patients who have already enrolled in previous study for 18 cytokine measurement have been excluded in current study [ 8 ]. The inclusion criteria from registration database for cytokine analysis were defined as: (1) onset symptoms and signs compatible with gMG; (2) immunotherapy naïve at baseline; (3) sero-positive for anti-AChR antibody; (4) MGFA clinical classification II to IV; (5) follow-up visits at 12 ± 6 months after baseline recruitment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through our single-center registration database, we reviewed the records of all patients with MG who were admitted to Huashan Hospital Fudan University from August 2013 to August 2020. The diagnosis of MG was based on clinical symptoms and at least one of the following specific tests: objective clinical response to neostigmine test, seropositivity for anti-AChR/anti-MuSK antibody, or significant decremental response on 3 Hz repetitive nerve stimulation ( 12 , 13 ). Other diseases that mimic MG were excluded, including Lambert-Eaton syndrome, motor neuron disease, and congenital myasthenic syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, T cell and cytokine profile may change during MG crisis. Huan et al demonstrated that patients with MG crisis had significantly elevated levels of Th17 as well as Th2-related cytokines IL-4 and IL-13 compared to 6 months post-ventilatory support [ 122 ]. Higher frequencies of Th1 and Th17 cytokines were also observed in MuSK-associated MG [ 123 ].…”
Section: Pathophysiologymentioning
confidence: 99%